GUT MICROBIOTA, PREBIOTICS, PROBIOTICS, AND SYNBIOTICS IN GASTROINTESTINAL AND LIVER DISEASES: PROCEEDINGS OF A JOINT MEETING OF THE BRAZILIAN SOCIETY OF HEPATOLOGY (SBH), BRAZILIAN NUCLEUS FOR THE STUDY OF HELICOBACTER PYLORI AND MICROBIOTA (NBEHPM), AND BRAZILIAN FEDERATION OF GASTROENTEROLOGY (FBG) - Barbuti, Ricardo Correa (2020)
Over the last years, there is growing evidence that microorganisms are involved in the maintenance of our health and are related to various diseases, both intestinal and extraintestinal. Changes in the gut microbiota appears to be a key element in the pathogenesis of hepatic and gastrointestinal disorders, including non-alcoholic fatty liver disease, alcoholic liver disease, liver cirrhosis, inflammatory bowel disease, irritable bowel syndrome, and Clostridium difficile - associated diarrhea. In 2019, the Brazilian Society of Hepatology (SBH) in cooperation with the Brazilian Nucleus for the Study of Helicobacter Pylori and Microbiota (NBEHPM), and Brazilian Federation of Gastroenterology (FBG) sponsored a joint meeting on gut microbiota and the use of prebiotics, probiotics, and synbiotics in gastrointestinal and liver diseases. This paper summarizes the proceedings of the aforementioned meeting. It is intended to provide practical information about this topic, addressing the latest discoveries and indicating areas for future studies.